A Study of Source Term Estimators in Coupled Finite-Volume/Monte-Carlo Methods with Applications to Plasma Edge Simulations in Nuclear Fusion: Analog and Collision Estimators (Communications in Computational Physics, 2025)
In many applications, such as plasma edge simulation of a nuclear fusionreactor, a coupled PDE/kinetic description is required. Such systems can be solvedwith a coupled finite-volume/Monte-Carlo method. Different procedures have beenproposed to estimate the source terms in the finite volume part that appear from theMonte Carlo part of the simulation. In this series of papers, we present a systematic(analytical and numerical) comparison of the variance and computational cost of a coherent set of such estimation procedures. The comparison is based on an invariantimbedding procedure, in which systems of ordinary differential equations (ODEs) arederived that quantify the statistical error and computational cost of each estimator. Inthis paper, we discuss analog and collision simulation and estimation procedures. Weanalyze in detail a scenario with forward-backward scattering in a one-dimensionalslab, uncovering and quantifying the effects determining the performance of the estimation procedures.
Keywords: Monte Carlo; reaction rate estimation; invariant imbedding; survival biasing; collision estimator.